2014
DOI: 10.1249/mss.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Passive Muscle Length Changes Affect Twitch Potentiation in Power Athletes

Abstract: The findings show that the effects of a conditioning MVC on twitch contractile properties are dependent on direction and velocity of ongoing muscle length changes. This may imply that functional enhancements from a conditioning MVC might be expected to be greatest for concentric muscle actions but are still present in isometric and eccentric parts of a movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…Significant enhancements in PT, RTD and RTR lasted for a minimum of one minute to a maximum of five minutes (Figures 2A, B and C). Such behavior is in line with previous findings (Fukutani et al, 2014; Gago et al, 2014b; Vandervoort et al, 1983) and indicates PAP related effects on the muscle contractile properties.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significant enhancements in PT, RTD and RTR lasted for a minimum of one minute to a maximum of five minutes (Figures 2A, B and C). Such behavior is in line with previous findings (Fukutani et al, 2014; Gago et al, 2014b; Vandervoort et al, 1983) and indicates PAP related effects on the muscle contractile properties.…”
Section: Discussionsupporting
confidence: 93%
“…extended versus flexed knee) on plantarflexor twitch PAP. While Fukutani et al (2014) investigated PAP of the plantarflexors in a flexed knee position to isolate the soleus muscle, others have used an extended knee position (Fukutani et al, 2013; Gago et al, 2014b; Vandervoort et al, 1983), but no one has compared PAP in a flexed and an extended position within the same subjects. Previous studies have indicated that flexing the knee changes the gastrocnemius muscle architecture resulting in impaired force transfer and neuromuscular inhibition of the gastrocnemius (Cresswell et al, 1995; Kawakami et al, 1998; Kennedy and Cresswell 2001; Tamaki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced PT and RTD together with reduced and RT 10-90 that recovered to baseline within 5 to 10 min after the end of the MVIC (Figs. 2 to 4) were expected and in support of previous studies (Baudry and Duchateau, 1394;Fukutani et al, 2013;Gago et al, 2014b;Jubeau et al, 2010). With the exception of the RT10-90 in the shortening mode (Fig.…”
Section: Post Activation Potentiation Of the Contractile Propertiessupporting
confidence: 91%
“…4), the conditioning affected twitch contractile properties in similar directions for all three modes. The magnitude and duration of potentiation did, however, vary between modes as it has previously been reported for the knee extensors and plantar flexors (Babault et al, 2008;Gago et al, 2014b).…”
Section: Post Activation Potentiation Of the Contractile Propertiesmentioning
confidence: 50%
See 1 more Smart Citation